Pulmonary Rehabilitation Using Regular Physical Exercise for the Management of Patients with Asthma - Elissa M McDonald; Felix S F Ram (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Background: Regular physical activity increases physical fitness and lowers ventilation during mild and moderate exercise thereby reducing the likelihood of provoking exercise-induced asthma. Regular exercise may also reduce the perception of breathlessness through a number of mechanisms including strengthening respiratory muscles. Subjectively, many asthmatics report that they are symptomatically better when fit, but results from trials have varied and have been difficult to compare because of different designs and training protocols.  Objectives: To assess evidence for the efficacy and effectiveness of regular physical training in patients with asthma. We searched the Cochrane database, Medline, Sportdiscus and Science citation index. Randomised trials in asthmatic patients undertaking regular physical training aged 7 years and older were considered for inclusion. Regular physical training had to involve at least 20 minutes, 2 to 3 times a week, over a minimum of four weeks.  Results: Eight studies could be included in this review. Physical exercise had no effect on resting lung function or the number of days of wheeze. Physical exercise improved cardiopulmonary fitness as measured by an increase in maximum oxygen uptake of 4.9 ml/kg/min (95% confidence interval 3.9 to 5.8). Regular exercise did not decrease any lung function measures. There were no data concerning quality of life measurements.  Conclusion: In patients with asthma, pulmonary rehabilitation using regular exercise improves cardiopulmonary fitness without changing lung function. There is no reason to withhold regular physical exercise in patients with asthma for the fear of deteriorating lung function. It is not known whether improved fitness is translated into improved quality of life.